The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1097/01.opx.0000180817.46312.0a
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and Reproducibility of Central Corneal Thickness Measurement With Pentacam, Orbscan, and Ultrasound

Abstract: In the assessment of normal corneas, the Pentacam measured CCT values closer to ultrasound pachymetry and with less variability compared with Orbscan. The (interobserver) reproducibility with the Pentacam was highest of all 3 modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
220
2
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(246 citation statements)
references
References 31 publications
15
220
2
9
Order By: Relevance
“…Ultrasonik yöntemler aras›nda ultrasonik pakimetre ve ultrasonik biyomikroskop (UBM), optik yöntemler aras›nda ise speküler mikroskopi, optik koherans tomografi, taray›c› slit kornea topografisi, konfokal mikroskopi ve Pentacam Scheimpflug sistem say›labilir. 1,[7][8][9][10][11][12][13][14][15][16][17] Ultrasonik pakimetri, ucuz ve kolay uygulanabilir bir teknoloji olmas›, ölçümlerinin yüksek tekrarlanabilirlikte ve güvenilirlikte olmas› nedeniyle klinik uygulamalarda yayg›n olarak kullan›lmaktad›r. 13,[18][19][20] Korneaya temas etmesi en önemli dezavantaj›d›r ve epitel defektlerine ve enfeksiyonlara yol açabilmektedir.…”
Section: Giriflunclassified
See 1 more Smart Citation
“…Ultrasonik yöntemler aras›nda ultrasonik pakimetre ve ultrasonik biyomikroskop (UBM), optik yöntemler aras›nda ise speküler mikroskopi, optik koherans tomografi, taray›c› slit kornea topografisi, konfokal mikroskopi ve Pentacam Scheimpflug sistem say›labilir. 1,[7][8][9][10][11][12][13][14][15][16][17] Ultrasonik pakimetri, ucuz ve kolay uygulanabilir bir teknoloji olmas›, ölçümlerinin yüksek tekrarlanabilirlikte ve güvenilirlikte olmas› nedeniyle klinik uygulamalarda yayg›n olarak kullan›lmaktad›r. 13,[18][19][20] Korneaya temas etmesi en önemli dezavantaj›d›r ve epitel defektlerine ve enfeksiyonlara yol açabilmektedir.…”
Section: Giriflunclassified
“…Son y›llarda kullan›ma giren OCULUS Pentacam cihaz› (Oculus Inc., Almanya), Scheimpflug prensiplerini kullanarak kornea ve lensin kesitsel görüntülerini almakta, ön segmentin 3 boyutlu katarakt yo¤unlu¤unu belirlemekte, kornea kurvatür ve kal›nl›¤›n› ölçmektedir. 1,11,17 Korneaya temas gerektirmemesi, h›zl› ölçüm almas›, kornean›n tüm lokalizasyonlar›nda-ki kal›nl›¤› belirlemesi ve yüksek tekrarlanabilirlikte olmas› en önemli avantajlar›ndand›r.…”
Section: Giriflunclassified
“…It includes a rotating Scheimpflug camera with a monochromatic slit light source. The device makes real-time images from the anterior segment of the eye, giving data with high repeatability and interoperator reproducibility (Lackner et al, 2005). The image gives a complete representation of the anterior chamber, extending from the endothelium of the cornea to the posterior surface of the lens.…”
Section: Measurement Of Ocular Parametersmentioning
confidence: 99%
“…This is justified, in part, by the position of the second principal plane of the cornea, which is close to the anterior surface (actually about 0.05 mm in front of the cornea). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 [6][7][8] In this way, the Pentacam-measured anterior chamber diameter (measured from anterior chamber angle to anterior chamber angle, AG m ) and corneal height (measured from the internal cornea to the line connecting the anterior chamber angles, H m ) can be used to calculate the theoretical corneal radius (R rt ). 6 Ho et al reported that…”
Section: -3mentioning
confidence: 99%